الممارسة الأنثروبولوجية بين الانتماء والنظرةعن بعد - بلحسن, مباركة (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
by choosingsomeexamplesanthropologistsmaghreb 's who have emerged in differentanthropologicaldomain:historical, social and religion by focusing on principlescharacteristics of this practice as: cultural specify, belongingsearcher and hisinterstingsubjects and the relationshipbetweenhis original communites and belongingfield and knowledgespacessociology and anthropology.